Possible simultaneous/integrated biological control of soil pests by mixed application of entomopathogenic and fungivorous nematodes - Ishibashi, N. (Saga Univ., Saga (Japan) Dept. of Applied Biological Sciences) (Malaysian Plant Protection Society, 2013)
Massive application of fungivorous nematode, Aphelenchus avenae, with 2 times 10 to the power of 5 per 500 ml of autoclaved soil in summer at 26-33 degree celsius and 5 times 10 to the power of 5 nematodes in autumn at 18-23 degree celsius effectively suppressed the preemergence damping-off of cucumber seedlings due to Rhizoctonia solani AG-by 80 percent and by 87 percent respectively. However, application of A. avenae more than 2 times 10 to the power of 5 nematodes caused leafminer-like symptoms on the cotyledons in fall season without any detrimental effects on the further plant growth. The simultaneous inoculation of root-knot nematode. Meloidogyne incognita and A. avenae in 1:1,000 ratio reduced the number of galls by 30-40 percent of M. incognita alone inoculation. similarly massive inoculation of entomopathogenic nematode, Steinernema feltiae also reduced the galls by M. incognita. Mixed application of A.avenae and S. feltiae suppressed the virulence of both R. solani and M. incognita, and removed the leafminer-like symptoms by A. avenae. since the beneficial nematodes are highly tolerant to conventional dosage of pesticides, mixed application with chemicals will be recommendable to integrated control of soil pests